Analysis of the cardiotoxic and myorelaxant effects of camphor on fish of the Nile tilapia species (Oreochromis niloticus) (Linnaeus 1758) - Clarissa Araújo da Paz; Suzane Maia de Oliveira; Maria Klara Otake Hamoy; Murilo Farias dos Santos; Anthony Lucas Gurgel do Amaral; Anara de Sousa Barbosa; Luciana Eiró-Quirino; Daércio José de Macedo Ribeiro Paixão; Luis André Luz Barbas; Dielly Catrina Favacho Lopes; Marcelo Ferreira Torres; Moisés Hamoy (Scientific Reports)
Abstract The present study aimed to characterize the behavior and evaluate the electromyographic (EMG), electrocardiographic (ECG), and respiratory responses of Nile tilapia (Oreochromis niloticus) when exposed to different concentrations of Camphor (CPR) as a potential anaesthetic in immersion and recovery baths. The goal was to determine the impact of CPR on muscle, cardiac, and respiratory functions, and assess its suitability as an anesthetic for tilapia. Therefore, juvenile fish (38.2 ± 5.5 g) were acclimatized in aquaria for 20 days under controlled environmental and water quality conditions. Four concentrations of CPR (150, 200, 250 and 300 mg L−1) were used in immersion baths to evaluate behavioral, EMG, ECG changes and recordings of opercular beats during the short-term treatment (5 min of exposure). The latency time for loss of the postural reflex was dependent on the CPR concentration. The EMG recordings demonstrated muscle activity during treatment and recovery. The ECG and opercular beat recordings demonstrated a decrease in heart and respiratory rates, with changes in the recorded tracings being more evident at higher concentrations. However, the use of a concentration of 300 mg L−1 makes the cardiac and respiratory effects more evident, with changes in the tracing, which can harm the animal’s hemodynamics. However, lower concentrations (150 mg L−1) showed tachycardia and opercular hypermotility, demonstrating changes not compatible with anesthesia. This article demonstrated that CPR in high concentrations can be harmful to the hemodynamics of tilapia, causing electrocardiographic and respiratory changes for a long period, even after recovery of muscular activity and postural reflex.